The use of modified polymeric polyhipe as an immobilized cell matrix - Jimat, Dzun Noraini; Azmi, Azlin Suhaida (IIUM Press, 2011)
Utilization of modified-polyHIPE polymer matrix in the immobilization cell system is probably can substitute conventional cell matrix. The confined microenvironment was designed to promote the bacterium growth and its metabolic activity. The applied forced-flow seeding technique yielded a more uniform distribution of cells within the polymeric support, which also helps to improve nutrient transport. This also prevents significant growth of cells around the outer surface of matrix. The microstructure of the matrix with respect to its physico-chemical characteristics, which include appropriate pore and interconnect sizes as well as surface chemistry (i.e. hydrophobic, hydrophilic), are very important with respect to the flow of nutrients and waste material and also for cell migration. As a result, the developed immobilized matrix can be performed effectively and essential in the area of bioprocess development specifically for microbial fermentations.